1978
DOI: 10.1590/s0034-89101978000400001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da infecção por Trypanosoma cruzi, em 1975, em dois bancos de sangue de Londrina, Paraná, Brasil

Abstract: Foi realizado inquérito sobre a positividade de reações sorológicas para o diagnóstico de tripanossomíase americana, em 4.500 candidatos a doadores não selecionados, atendidos em 1975, em dois bancos de sangue de Londrina, Paraná, Brasil. Observou-se resultado positivo da reação de fixação do complemento em 299 (7,9%) dos 3.774 candidatos a doadores atendidos no Banco de Sangue do Hospital Universitário (indivíduos residentes predominantemente na zona rural), tendo também sido positivos os resultados da reação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Chagas' disease occurs most frequently in the northern region of the state (5). During the 1970s a prevalence of 7.4% was found among blood bank donors (6), and a study in the 1990s found that 6.3% of residents in northwest Paraná had positive serology (7). According to Silveira and Vinhaes (2), the National Health Foundation (NHF) did not report triatomine detection in domestic environments in the state in 1995 and 1997.…”
mentioning
confidence: 99%
“…Chagas' disease occurs most frequently in the northern region of the state (5). During the 1970s a prevalence of 7.4% was found among blood bank donors (6), and a study in the 1990s found that 6.3% of residents in northwest Paraná had positive serology (7). According to Silveira and Vinhaes (2), the National Health Foundation (NHF) did not report triatomine detection in domestic environments in the state in 1995 and 1997.…”
mentioning
confidence: 99%
“…A maioria destes triatomíneos foi encontrada em municípios do norte próximos à divisa com o Estado de São Paulo, para onde ocorreu uma intensa migração, principalmente de mineiros, na primeira metade deste século. N a d é c a d a d e 7 0 , f o i o b s e r v a d a u m a prevalência global de 7,4% entre doadores em bancos de sangue de Londrina, norte do Estado 3 .…”
unclassified
“…Furthermore, according to the Coordination of Blood and Hemoderivates of the Ministry of Health this figure for the state as whole had decreased to 0.86% in 1995 6 . In the city of Londrina, data collection carried out by various authors in the years of 1958, 1975, 1996 and 1998, found a decreasing seroprevalence of 6.92%, 7.49%, 1.4% and 1.3%, respectively 4,5,31,32 . Nowadays, with the main way of transmission under control, the principal concern is regarding assistance to infected individuals, particularly their situation in the job market, the social services involved and the necessity for adequate medical care 18 .…”
Section: Introductionmentioning
confidence: 99%